Characteristics of Older Adults Associated with Patient–Provider Communication About Health Improvement in the United States - Ingrid Wu; Susan B. Quelly; Zhuo Chen; Boon Peng Ng (Journal of Ageing and Longevity, 2025)
Shared decision making is a key part of patient-centered care and is associated with improved quality of care. The objective was to analyze associations between sociodemographic factors, health conditions, and how frequently providers ask Medicare beneficiaries about ideas to improve their own health. The 2020 Medicare Current Beneficiary Survey, a nationally representative dataset of beneficiaries aged ≥65 years, was analyzed (n = 7416). A survey-weighted multinomial logistic model was performed to analyze associations between independent variables and a three-level categorical dependent variable. Approximately 28.6%, 22.9%, and 48.5% of beneficiaries reported never (reference group), sometimes, and usually/always being asked about their own ideas for improving health, respectively. Beneficiaries aged 65–74 were more likely to usually/always or sometimes be asked for ideas about health improvement than those aged ≥75. Beneficiaries with lower than a high school education were less likely to be asked about ideas to improve their health than those with more than a high school education. Beneficiaries living alone were less likely to be asked about their health improvement ideas than those living with others. Disparities involving how often providers asked questions for shared decision making among beneficiaries were observed. Increasing provider awareness and implementation of standardized shared decision-making models may begin to mitigate these disparities.